Mengajarkan Ayah, Menjadi Pribadi yang Lebih Baik: Refleksi dan Nilai Pendidikan dalam buku "Ajari Ayah, Ya Nak!" Karya Reza Indragiri Amriel - Aji Sari Nusetyawati (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Reza Indragiri Amriel's book "Ajari Ayah, Ya Nak!" was published in 2014 and offers a fresh perspective on the crucial role of parents, particularly fathers, in educating and guiding their children. The author invites readers to consider how father-child interactions can become a process of mutual learning, with a focus on the father's role as an educator and how children learn from their own experiences. The aim of this abstract is to examine the messages and values contained in the book, as well as its connection to the progress of family education in Indonesia. The book emphasizes the importance of fathers being actively involved in their children's education and how this can influence their character in the future. This article seeks to understand how Reza Indragiri Amriel portrays the role of fathers in family education and how this influences the personal development of children. We do so by employing a qualitative approach. The findings are expected to provide readers with an understanding of the importance of parental collaboration in educating their children.